Exploring network governance in sustainable beekeeping management in the Mekong subregion and its challenges - Punya, Supitcha; Sinpoo, Chainarong; Phokasem, Patcharin; Disayathanoowat, Terd (Frontiers in Sustainable Food Systems, 2024)
This research paper aims to explore a network governance in sustainable apiculture management and identify its challenges to government and non-governmental policy makers. Qualitative data was collected through participant observation during field visits and Focus Group Discussions (FGDs) with regional apiculture management. The research results show that each country in the Mekong subregion has different network governances in supporting a sustainable apiculture management. Some countries have a collaborative network between the government, the civil society, entrepreneurs, and scholars. In contrary, some countries lack a policy framework from the government. This difference becomes challenges for the six governments of the Mekong subregion countries to commonly support the sustainable apiculture management in the subregion. The identified challenges in the paper are: (1) a capacity gap between the six countries of the region; (2) no common policies and regulations that would facilitate local beekeepers’ access to wider regional bee products; (3) no support for inter-regional transport of bees and honey for academic purposes; (4) inadequate native bee species preservation and pesticides use; (5) local beekeepers’ limited access to a regional bee diseases and pesticides use database; and, (6) a lack of regional standards for general honeybee product support.